EKSISTENSI KOMUNITAS BUGIS DI KERAJAAN PAGATAN DAN KUSAN, KALIMANTAN SELATAN - Andi Nuralang (WalennaE, 2001)
Bugis migrants were the pioneer of Pagatan Kingdom in South Kalimantan which integrated by Kusan Kingdom by Arung Abdulkarim. Bugis community pocket at Pagatan was pioneered by Penna Dekke, a wealthy ruler of Soppeng, who later on established a kingdom. Bugis existence at Pagatan and Kusan was proved with artifacts and monument finds. Archaeological findings at formerly Bugis settlement pockets are still able to be found. Even the living Bugis culture remains practice by the community, such as its language and religion.